جودة اللغة العربية في الإذاعات المحلية - جنيدي,فاطمة الزهراء; الأصفر,ياسمين (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسةإلى التعرف على جودة اللغة العربية في الإذاعات المحليةمن خلال الدراسة ميدانية للأساتذة اللغة العربية واعلام واتصال وذلك من خلال إشكالية بحثية تتمحورفي جودة اللغةالعربية في الإذاعات المحلية ولهذا الغرض ا عتمدناعلى أداة من أدوات البحث العلمي ممثلةفي الاستبيانات لذي وزعت60استمارة على الاساتذة،وقد تم الرد على 38 استمارة فقط، بغرض التأكد من التساؤلات المطروحة. انتهت الدراسةإلى مجموعةمن النتائج أهمها ضرورة اهتمام باللغة العربية في المجال الاعلام، وتكوين دورات مستمرة من اجل تفادي الأخطاء اللغوية، وتقريب الحوار في المسرح والتمثيليات في صياغة اللغوية، والعمل على ترقيتها الى اللغة الفصحى . This study aims to identify the quality of the Arabic language on local radio stations through a field study of Arabic language, media and communication professors through a research problem centered on the quality of the Arabic language on radio stations Local For this purpose, we relied on a scientific research tool represented in the questionnaire, which was distributed to 60 questionnairesProfessors, for the purpose of verifying the questions asked The study concluded with a set of results, the most important of which is the necessity of paying attention to the Arabic language in the field of media, creating continuous courses in order to avoid linguistic errors, bringing dialogue in theater and plays closer to linguistic formulation, and working to upgrade them toClassical language
من وجهة نظر أساتذة علوم الاعلام والاتصال والادب العربية
Keywords: الإذاعة المحلية; جودة اللغة العربية; Arabic language; local radio; quality of Arabic language